INSULIN-INDUCED WEIGHT GAIN AS A POTENTIAL RISK FACTOR FOR CARDIOVASCULAR DISEASE: A NARRATIVE REVIEW. - Jha, Mithilesh (Student’s Journal of Health Research Africa, 2024)
Diabetes mellitus, a chronic metabolic disorder characterized by high blood glucose levels, is a significant global health concern. Insulin therapy, essential for managing diabetes, is often linked with weight gain. This weight gain, while beneficial in some patients, poses risks for overweight or obese individuals, particularly in terms of cardiovascular disease (CVD), the leading cause of mortality in this population. This review aims to combine current research on the relationship between insulin-induced weight gain and cardiovascular disease risk, exploring mechanisms, clinical implications, and management strategies. The several pathways of insulin-induced weight gain are covered in the review, including impacts on anabolism, increased adiposity, and fluid retention. It explores the pathophysiological mechanisms that relate weight gain to cardiovascular disease (CVD), including endothelial dysfunction and oxidative stress, and looks at how weight gain impacts cardiovascular risk factors like hypertension, dyslipidemia, and inflammation. In addition, the review assesses data from clinical trials and epidemiological studies, contrasting various insulin dosage schedules and their relationships to CVD outcomes. Lastly, it discusses how to control weight gain while on insulin therapy, with a focus on dietary changes, exercise, medication modifications, and patient education. The review highlights the need for further research to clarify the causal relationships and to develop more effective strategies for managing weight gain in insulin-treated patients. It suggests exploring personalized medicine approaches and newer pharmacological agents to optimize diabetes care while minimizing cardiovascular risks. This review underscores the importance of incorporating weight management into the clinical management of diabetes. It advocates for a holistic approach that includes regular monitoring, patient education, and tailored treatment plans to mitigate cardiovascular risks associated with insulin-induced weight gain.